A sophisticated logic of enhancement: a disability-sensitive, welfare-maximizing stance in philosophy of medicine and procreative ethics - Law, David Benjamin, author; Gorin, Moti, advisor; McShane, Katie, committee member; Hickey, Matthew, committee member (Colorado State University. Libraries, 2024)
Julain Savulescu and Guy Kahane have developed a compelling yet controversial set of arguments that provide a theoretical and action-guiding grounding for the fields of medicine and procreative ethics. In medicine, they argue that medicine should do much more than merely treat patients; instead, it should "enhance" them to enjoy the greatest possible welfare. They argue that enhancement is justified by the same moral principles that justify treating patients in a medical setting. Similarly, in procreative ethics, they contend that when pre-natal selection is available, a similar welfare-maximizing principle should inform what children we should bring into existence. They argue that the "most advantaged child" among those that could be selected ought to be selected. There is something deeply compelling about these arguments but also deeply concerning; we should, of course, want the greatest welfare for ourselves, others, and our children, but we should also worry that accomplishing these ends via medicine and procreative selection may be using inappropriate means, relay implicit prejudices, or even constitute a kind of eugenics. In this thesis, I interrogate Savulescu and Kahane's arguments for the logic of enhancement and argue that a compelling and largely cohesive view emerges that has significant implications for the philosophy of medicine and procreative ethics. The view is, however, imperfect. Several adjustments and compromises must be made to make the view fully cohesive and to accommodate the highly compelling arguments made by disability rights theorists. In suggesting these adjustments and compromises, I ultimately defend the logic of enhancement from its most potent objections and contend that it is a highly illuminating view for ethical and theoretical work in the philosophy of medicine and procreative ethics.
Keywords: health and disease; justice; procreative beneficence; human enhancement; disability; philosophy of medicine